2016
DOI: 10.1097/prs.0000000000002229
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Full and Short-Scar Face-Lift Incision Techniques in Multiple Sets of Identical Twins

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Comparing the facial appearance of MZ twins who have undergone different procedures is an ideal approach to this question. Outcomes from such efforts were undertaken by New York surgeon Dr Darrick E. Antell and colleagues (2016), who performed various face-lift procedures on four sets of MZ twins (three female and one male) and one set of MZ triplets (female). The twins ranged in age from 56 to 73 years at the time of surgery.…”
Section: Face-lift Technique Comparison In Identical Twinsmentioning
confidence: 99%
“…Comparing the facial appearance of MZ twins who have undergone different procedures is an ideal approach to this question. Outcomes from such efforts were undertaken by New York surgeon Dr Darrick E. Antell and colleagues (2016), who performed various face-lift procedures on four sets of MZ twins (three female and one male) and one set of MZ triplets (female). The twins ranged in age from 56 to 73 years at the time of surgery.…”
Section: Face-lift Technique Comparison In Identical Twinsmentioning
confidence: 99%
“…Over the past two decades, authors of several standard textbooks have recommended MFL for parotid abscess drainage (PAD), and MBI should be performed only in case of caudally extending/locating PA ( 1 , 4 , 8 , 9 , 10 ). Minimally invasive surgical techniques result in gratifying outcomes, low complications rates, and rapid return to daily activities ( 11 , 12 , 13 , 14 ). However, our literature search unveiled a truth that the recommendation on surgical approach to PA relied on Level of Evidence IV and V after the Oxford Centre of Evidence-Based Medicine (CEBM).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In addition to traditional face-lift methods involving the excision and tightening of skin and the underlying soft tissues, 3 ancillary procedures have become paramount in achieving an optimal result. 4 Prior studies have shown no difference in aesthetic outcome with respect to face-lift technique, 5 but autologous fat grafting and ancillary procedures in facial rejuvenation are performed routinely and safely to address signs of aging and achieve a better aesthetic outcome. 611…”
Section: Introductionmentioning
confidence: 99%